NVMRA: utilizing NVM to improve the random write operations for NAND‐flash‐based mobile devices. (8th December 2015) - Chen, Renhai; Shen, Zhaoyan; Ma, Chenlin; Shao, Zili; Guan, Yong
Summary: NAND flash memory has become the major storage media in mobile devices, such as smartphones. However, the random write operations of NAND flash memory heavily affect the I/O performance, thus seriously degrading the application performance in mobile devices. The main reason for slow random write operations is the out‐of‐place update feature of NAND flash memory. Newly emerged non‐volatile memory, such as phase‐change memory, spin transfer torque, supports in‐place updates and presents much better I/O performance than that of flash memory. All these good features make non‐volatile memory (NVM) as a promising solution to improve the random write performance for NAND flash memory. In this paper, we propose a non‐volatile memory for random access (NVMRA) scheme to utilize NVM to improve the I/O performance in mobile devices. NVMRA exploits the I/O behaviors of applications to improve the random write performance for each application. Based on different I/O behaviors, such as random write‐dominant I/O behavior, NVMRA adopts different storing decisions. The scheme is evaluated on a real Android 4.2 platform. The experimental results show that the proposed scheme can effectively improve the I/O performance and reduce the I/O energy consumption for mobile devices. Copyright © 2015 John Wiley & Sons, Ltd.